A NEEDS ANALYSIS OF READING MEDIA THAT SUPPORT BEHAVIORAL READING ENGAGEMENT AND SDG 16 VALUES AT TELKOM KINDERGARTEN SINGARAJA - I Komang Dodi Riantawan; Putu Kerti Nitiasih; Luh Gd Rahayu Budiarta (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT Reading experiences in early childhood are shaped not only by the availability of storybooks but also by the extent to which reading media encourage children's active participation during shared reading. This issue remains evident in several kindergarten classrooms, where existing reading materials have yet to fully support interaction, engagement, or the integration of social values aligned with Sustainable Development Goal (SDG) 16. In response to this context, the present study aimed to identify teachers' and children's needs for reading media capable of fostering behavioral reading engagement while simultaneously incorporating the values of Peace, Justice, and Strong Institutions within classroom learning. A descriptive qualitative approach was employed involving one classroom teacher and 20 children aged 5–6 years at Telkom Kindergarten Singaraja. Data were collected through classroom observations and semi-structured interviews, then organized into the categories of learning needs and target needs prior to descriptive analysis. The findings revealed that the existing reading media had not adequately facilitated interactive shared reading, resulting in limited behavioral engagement among children during literacy activities. The needs analysis identified several essential characteristics of future reading media, including a large-format design, attractive illustrations, contextual and interactive stories, simple bilingual content, and the integration of SDG 16 values. This study proposes a needs-based framework for developing reading media that integrates behavioral reading engagement, bilingual learning, and SDG 16 values, providing a conceptual foundation for literacy media development in early childhood education. ABSTRACT Pengalaman membaca pada anak usia dini tidak hanya dipengaruhi oleh keberadaan buku cerita, tetapi juga oleh sejauh mana media yang digunakan mampu mendorong keterlibatan aktif selama proses shared reading. Kondisi tersebut masih menjadi tantangan di beberapa kelas taman kanak-kanak karena karakteristik media yang tersedia belum sepenuhnya mendukung interaksi, partisipasi, maupun pengenalan nilai-nilai sosial yang relevan dengan Sustainable Development Goals (SDG) 16. Atas dasar itu, penelitian ini diarahkan untuk mengidentifikasi kebutuhan guru dan anak terhadap media membaca yang mampu memperkuat behavioral reading engagement sekaligus mengintegrasikan nilai-nilai Peace, Justice, and Strong Institutions pada konteks pembelajaran di TK Telkom Singaraja. Pendekatan kualitatif deskriptif diterapkan dengan melibatkan satu orang guru dan 20 anak usia 5–6 tahun. Informasi diperoleh melalui observasi kegiatan membaca dan wawancara semi-structured, kemudian diorganisasi ke dalam kategori learning needs dan target needs sebelum dianalisis secara deskriptif. Temuan memperlihatkan bahwa media membaca yang digunakan belum sepenuhnya mendukung interaksi selama shared reading, sehingga keterlibatan anak dalam mengikuti kegiatan membaca masih terbatas. Analisis kebutuhan mengarah pada karakteristik media berupa buku berukuran besar, ilustrasi yang menarik, cerita kontekstual dan interaktif, konten bilingual sederhana, serta integrasi nilai-nilai SDG 16. Penelitian ini menghasilkan landasan empiris bagi pengembangan media membaca yang menghubungkan penguatan literasi, pembentukan karakter, dan peningkatan behavioral reading engagement dalam pembelajaran anak usia dini.